Peningkatan Kreativitas Belajar Matematika MelaluiPengembangan Lks (Lembar Kerja Siswa) Berbasis Problem Posing (PTK di Kelas VII SMP Negeri 11 Surakarta Tahun Ajaran 2014/2015) - Permatasari, Balinda Suci; , Drs. Slamet HW, M.Pd (2015)
This research to purpose inspect and describe level creativity the students in mathematic s teaching with development LKS basically Problem Posing. This research is qualitative research of students in VII E class of Junior High School 11 of Surakarta 2014/ 2015 are 23rd students. The data collecting by observation methode, test, field datum, and documentation. Technique data analysis in a qualitative descriptive with interactive analysis occur of collecting data, reduction data, presentation data and drawing conclusion. The research result to show creativity the students advance envelop aspect : a) the students present a question to the teacher before action 12, 12 % and after action 51, 51 % , b) the students can individual work when teaching before action 24,24% and after action 54,54%, c) the students refers to an opinion in a spontaneous before action 15,15 % and after action 57,57 %, 4) the students to show thinking and idea problem solving before action 18,18% and after action 45,45%. This research conclusion that application development LKS basically Problem Posing can increase creativity the students in mathematic teaching.